ZnO nanocrystals and allied materials - Okada, Tatsuo; Rao, M S Ramachandra (Springer Series in Materials Science, 2014)
ZnO has been the central theme of research in the past decade due to its various applications in band gap engineering, and textile and biomedical industries. In nanostructured form, it offers ample opportunities to realize tunable optical and optoelectronic properties and it was also termed as a potential material to realize room temperature ferromagnetism. This book presents 17 high-quality contributory chapters on ZnO related systems written by experts in this field. These chapters will help researchers to understand and explore the varied physical properties to envisage device applications of ZnO in thin film, heterostructure and nanostructure forms.